In-field characterization of key performance parameters for bifacial photovoltaic installation in a desert climate. (October 2020) - Baloch, Ahmer A.B.; Hammat, Said; Figgis, Benjamin; Alharbi, Fahhad H.; Tabet, Nouar
Abstract: To address the main challenges inhibiting the adoption of bifacial PV technology in hot desert environment, continuous performance monitoring and comprehensive analyses are timely required. Therefore, for strengthening its bankability, this techno-economic study presents an in-field bifacial parametric analysis for the environment of Middle-East. Impacts of ground coverage ratio (GCR), stand-alone/in-array mounted losses, albedo, module temperature, mounting height, tilt, and azimuth angle were quantified. To highlight the bifacial potential, economic analysis as a function of energy gain and investment premium was carried out for demarcating profitable operating zones. Moreover, multi-variable analysis for rear irradiance was performed using ground coverage ratio, height, albedo and array size, specifically:1 × 1 (free-standing module), 3 × 3 and 5 × 5. It was found that for systems where the land costs are significant, high GCR coupled with increased mounting height would result in a better energy yield per area. Module with a bifacial gain of 8.6% was found to be profitable provided that the bifacial premium investment doesn't exceed 10% of monofacial. Thermally, bifacial power gain was found to determine the cell temperature under different irradiation conditions. The study reveals vital insights that will allow engineers and researchers to optimize bifacial PV performance in hot and sunny desert climates. Highlights: In-array bifacial PV gained a maximum of 16.3% more energy yield than monofacial. From 1 × 1 to 5 × 5 array size, the reduction in bifacial gain ranged from 11.0 to 40.9%. Bifacial module temperature depended on temporal distribution of albedo radiation. Module of bifacial gain 8.6% is only profitable if premium capital stays under 10%.